Boosting babies: Singapore’s drive to raise birth rates - Varghese, Susheela A. (Institutional Knowledge at Singapore Management University, 2012)
The Boosting Babies case is a persuasion case that demonstrates the interweaving of source, receiver and context that persuaders must grapple with as they try to change attitudes and actions. It raises a dilemma faced in Singapore and many other developed nations around the world where fewer young people are getting married and having children. The Singapore government now finds itself in a position where it is trying to influence its young married couples to have more children. After vigorously discouraging citizens from having too many children in the 1960s and 1970s, Singapore observed that total fertility rate (TFR) fell rapidly in the early 1980s. Singapore then responded with a variety of economic and education incentives for mothers, particularly for working graduate mothers. Social matchmaking measures were also fostered through the Social Development Unit (SDU). Still, birth rates have fallen to below-replacement total fertility rates. Lim Soon Hock, chairman of the National Family Planning Council since 2006, and his committee have targeted youth as the audience for the 2011 campaign initiatives. They are struggling to think of new measures that will encourage young people to have children. They approach a Persuasion class at the Singapore Management University with a brief to come up with some new ideas targeted at persuading youth to start thinking about family as an important aim in life.